Thermal inactivation D- and z-values of Salmonella Enteritidis and Salmonella Typhimurium in whole-muscle beef - Dora-Liyana, Abd Lataf; Mahyudin, Nor Ainy; Ismail-Fitry, Mohammad Rashedi; Ahmad Zainuri, Mohd Dzomir (Malaysian Society of Applied Biology, 2023)
Salmonella spp. is a significant foodborne pathogen present in raw meat products and in the processing environment. It can be eliminated by thermal processes such as cooking. Time and temperature in the thermal process play an important role in eliminating this pathogen. The objective of this study is to determine the D- and z-values of Salmonella spp. in whole-muscle beef using the isothermal inactivation method in four temperatures at designated time intervals. Whole-muscle beef was inoculated with 7 to 8 log10 CFU/mL of Salmonella Typhimurium and Salmonella Enteritidis. The inoculated meat samples were heat treated at 58 °C, 60 °C, 62 °C, and 64 °C. At each temperature, Salmonella spp. survival rate was plotted and the D- and z-values were obtained by linear regression of the survival curve. The D-values for the thermal inactivation of whole-muscle beef are D58 °C=5.41 min, D60 °C=2.03 min, D62 °C=0.46 min, and D64 °C=0.18 min, while the z-value obtained was 3.94 °C. These findings will assist food processors in designing the critical limits on the critical control points of the cooking process that ensure safety against Salmonella spp. in cooked whole-muscle beef.